تأثير برنامج تدريبي باستخدام التدريب البليومتريك على تنمية القوةالانفجارية لعضلات الرجلين للاعبي الكرةالطائرة - الكرمدي, عارف صالح محسن (Journal of Sport Science Technology and Physical Activities, 2025)
This research aims to design a training program using Plyometric training for volleyball players the Republic of Yemen and the study of its impact on the physical variables (characteristic strength fast - explosive power) to the muscles of the two men for volleyball players. The researcher assumed to have a statistically significant differences between the averages of tribal and dimensional measurements in the distinctive force variables speed and explosive power in favor of averages dimensional measurements of the volleyball players. After selecting the original community of the study, which represents a first-class players for the club Al Ahli in Hodeidah Governorate and strong 12-man squad and given the nature of the experimental approach used was selected sample Find the way intentional. The researcher conducting homogeneity among respondents in key variables (age, height, weight, age training) and determine the most appropriate physical tests and the duration of the training program and the number of training units per week and time of the training unit. It has been reached and there are significant differences between the two measurements pre and post experimental group research sample in physical tests of the explosive force of the muscles of the two men for the benefit of telemetric.